2008
DOI: 10.1016/j.ejphar.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serotonin-toxicity syndrome (toxidrome) elicited by 5-hydroxy-l-tryptophan in clorgyline-pretreated rats

Abstract: Patients are at high risk of developing serotonin-toxicity syndrome (toxidrome) when they take multiple serotonergic drugs, particularly co-administered with monoamine oxidase inhibitors or 5-hydroxytryptamine (5-HT) reuptake blockers. The toxidrome can vary from mild to severe. The primary goal of the present study was to understand the relationship between behavioral signs and degrees of toxidrome induced by 5-hydroxy-L-tryptophan (5-HTP) in clorgylinized rats. The severity was obtained by scoring behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 37 publications
7
61
1
Order By: Relevance
“…Behavioral syndrome was scored according to an established method described in our previous work (Ma et al, 2008). Scoring was performed 30 - 60 min after MDMA or vehicle administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral syndrome was scored according to an established method described in our previous work (Ma et al, 2008). Scoring was performed 30 - 60 min after MDMA or vehicle administration.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements and data analysis procedures were similar to our previous work (Ma et al, 2008) with minor modifications. Rats were allowed to acclimatize to the temperature-controlled measurement chamber for at least a 2 h period prior to obtaining body temperature measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Our studies further demonstrated that a 10-fold increase in 5HT ext was sufficient to cause a mild syndrome, showing hypothermia, head shakes and myoclonus but no signs indicative of advanced or severe syndrome (e.g., tremor, forepaw treading or hindlimb abduction) (Ma et al, 2008;Zhang et al, 2009). This suggests that the brain is most likely intolerant of the double digit increase in 5HT ext in terms of fold-change in the cerebrospinal fluid.…”
Section: Dangerous Elevations Of 5ht Ext : How Much 5ht Ext In the Cnmentioning
confidence: 75%
“…To simplify the analysis, 5HT precursors (e.g., 5HTP) in combination with MAOI (e.g., clorgyline) are more applicable for elucidating the 5HT threshold. Many studies have demonstrated that a single injection of 5HTP combined with clorgyline was sufficient to produce a dose-dependent increase in 5HT ext in the brain, causing serotonin syndrome (Ma et al, 2008;Nisijima et al, 2004;Nisijima et al, 2000;Nisijima et al, 2001;Shioda et al, 2004). To obtain the threshold level of 5HT ext , we designed a 5HTP dosing regimen in clorgyline-pretreated rats.…”
Section: Dangerous Elevations Of 5ht Ext : How Much 5ht Ext In the Cnmentioning
confidence: 99%
See 1 more Smart Citation